Preparation and Characterization of MCM‐41@PEI·Mn as a New Organic–Inorganic Hybrid Nanomaterial and Study of its Catalytic Role in the Oxidation of Cyclohexene, Ethyl Benzene, and Toluene in the Presence of H2O2 as an Oxidant. (16th March 2016) - Tarasi, Roghayeh; Ramazani, Ali; Ghorbanloo, Massomeh; Khoobi, Mehdi; Aghahosseini, Hamideh; Joo, Sang Woo; Shafiee, Abbas
Abstract : The manganese‐containing mesoporous nanomaterial (MCM‐41@PEIMn) was synthesized and used as a catalyst for the oxidation of cyclohexene, ethyl benzene, and toluene. The mesoporous MCM‐41 was prepared via hydrothermal method and then polyethylenimine as a reactive surface modifier was grafted on its surface in the presence of ([3‐(2, 3‐epoxypropoxy)propyl] trimethoxysilane) as a grafting agent. Manganese(ii ) acetate was loaded onto the prepared MCM‐41@PEI. The MCM‐41, MCM‐41@PEI, and MCM‐41@PEI.Mn were characterized and elucidated by Fourier transform infrared, powder X‐ray diffraction, thermogravimetric, N2 adsorption–desorption, energy‐dispersive X‐ray spectroscopy, scanning electron microscopy, and transmission electron microscopy techniques. The catalytic activity and selectivity of the MCM‐41@PEI.Mn in the oxidation of cyclohexene, ethyl benzene, and toluene with 30% aqueous H2 O2 as an oxidant were studied. Furthermore, the influences of various parameters such as temperature, oxidant amount, catalyst reusability, and kinds of solvents have been studied. The results showed that the manganese‐containing mesoporous nanomaterial was easily separated from the reaction mixture and reused at least five times without noticeable loss of activity. Abstract :